Alterations of antitumor and metabolic responses in L5178Y-R lymphoma-bearing mice after only 30-minute daily chronic stress exposure - Caballero-Hernandez, D.; Najera-Valderrabano, D.; Valadez-Lira, A.; Franco-Molina, M.; Gomez-Flores, R.; Tamez-Guerra, P.; Tamez-Guerra, R.; Rodríguez-Padilla, C. (Experimental Oncology, 2017)
Aim: In stress research, reducing times of stress induction may contribute to improving the well-being of experimental animals, especially in cancer models, already under physiological distress. To support this idea, we evaluated the effects of a short-timed stress protocol on endocrine, metabolic and immune indicators in mice bearing the L5178Y-R lymphoma. Materials and Methods: A 30-minute daily stress protocol was applied for 28 days to healthy and lymphoma-bearing BALB/c mice; body weight, plasma levels of corticosterone, norepinephrine, Th1/Th2 cytokines, insulin, and leptin, were measured. Results: We found a 12% significant decrease in body weight in non-tumor bearing mice under stress (p < 0.007). The disruption of weight evolution was accompanied by a stress induced 85% decrease in plasmatic leptin (p < 0.01) and total reduction of insulin. Tumor burden alone was associated to an increase in more than two-fold of plasmatic levels of norepinephrine (p < 0.008). Neither stress nor tumor or their combination, resulted in an elevation of systemic IL-6. IFN-γ levels were 20 times higher in lymphoma-bearing animals when compared with non-tumor bearing mice (p < 0.01); however, under stress, this response was reduced by half, indicating a suppressing effect of chronic stress on the antitumor immune response. Conclusion: A short-timed stress induction is enough to cause significant alterations in the metabolism and immunity of healthy and tumor-bearing mice, supporting the use of short-timed protocols as an efficient way to induce chronic stress that also considers concerns regarding the well-being of experimental animals in biomedical research.